History of parvovirus B19 infection is associated with silent cerebral infarcts. Issue 1 (17th August 2017) - Ogunsile, Foluso J.; Currie, Kelli L.; Rodeghier, Mark; Kassim, Adetola; DeBaun, Michael R.; Sharma, Deva
Abstract: Background: The relationship between silent cerebral infarcts (SCIs) and history of parvovirus B19 (B19V) has not been systematically evaluated. As an ancillary study from the Silent Cerebral Infarct Trial (SIT) (NCT00072761), we tested the hypothesis that a history of B19V infection is associated with an increased prevalence of SCIs in children with sickle cell anemia. Procedure: We used a retrospective cross‐sectional cohort study design; each participant underwent a brain magnetic resonance imaging (MRI) scan and medical record review for prior B19V infection (n = 958). Results: SCI was present in 30% (287 of 958) of participants and 17% (165 of 958) had a history of B19V infection. Based on prior evidence that low baseline hemoglobin (Hgb) levels are associated with increased odds of SCI, Hgb levels were divided into tertiles (<7.6 g/dl, ≥7.6–≤8.5 g/dl, ≥8.6 g/dl) and multivariable analysis was used to determine the relationship between the joint effect of prior B19V infection, Hgb levels, and SCI. Prior B19V infection and the lowest Hgb tertile were associated with increased risk of SCI (odds ratio [OR] 2.12; 95% CI, 1.17–3.84; P  = 0.013); no prior B19V infection and the highest Hgb tertile were associated with a decreased risk (OR 0.56; 95% CI, 0.38–0.84; P  = 0.004). Conclusions: Efforts to decrease the incidence of B19V infection, such as the development of a B19V vaccine, may decrease SCI prevalence.